Fermentative and nutritional characteristics of pineapple plant straw silage - López Herrera, Michael (2008)
Nutritional value and fermentative parameters of pineapple straw (leaves, shoots and stems) in non fermented and fermented material were determined. Microsilages were made with 1 kg polyethylene bags. Dried citrus pulp (DCP) at 0, 5, 10, and 20% of fresh weight, 3% molasses, and a bacterial inoculum at (1.0 l.t-1) were added to plant straw. Pineapple straw without additives was also evaluated. Nutritional value of pineapple straw fermented and non-fermented, changed according to carbohydrate inclusion. CP, NDF, ADF, lignin, ashes, N-NH3.N-total-1, buffer capacity, and pH value decreased when carbohydrate concentration (molasses and DCP) was high. On the other hand, when DCP was high, DM, EE, IVDMD and NFC content of forage increased, as well as energy density. Using a simulation, it was determined that pineapple straw silage (20% DCP), without protein restriction, could fill energy requirements of 350 kg steers with body weight gains of 500 g.day-1and a milk production up to 25 kg.day-1 with 4% fat milk in lactating dairy cows weighting 450 kg, not counting the ruminal passage rate. DM cost of 1 kg of pineapple straw silage, with or without additives, ranges from ¢3.95 to ¢20.8. Then, pineapple straw silage is an alternative for ruminant animal supplementation due to its nutritional profile and elaboration low cost.